Low-Dose Aspirin Augments the Anti-Inflammatory Effects of Low-Dose Lithium in Lipopolysaccharide-Treated Rats - Rachel Shvartsur; Galila Agam; Sarit Uzzan; Abed N. Azab (MDPI AG, 2022)
Mounting evidence suggests that immune-system dysfunction and inflammation play a role in the pathophysiology and treatment of mood-disorders in general and of bipolar disorder in particular. The current study examined the effects of chronic low-dose aspirin and low-dose lithium (Li) treatment on plasma and brain interleukin-6 and tumor necrosis factor-α production in lipopolysaccharide (LPS)-treated rats. Rats were fed regular or Li-containing food (0.1%) for six weeks. Low-dose aspirin (1 mg/kg) was administered alone or together with Li. On days 21 and 42 rats were injected with 1 mg/kg LPS or saline. Two h later body temperature was measured and rats were sacrificed. Blood samples, the frontal-cortex, hippocampus, and the hypothalamus were extracted. To assess the therapeutic potential of the combined treatment, rats were administered the same Li + aspirin protocol without LPS. We found that the chronic combined treatment attenuated LPS-induced hypothermia and significantly reduced plasma and brain cytokine level elevation, implicating the potential neuroinflammatory diminution purportedly present among the mentally ill. The combined treatment also significantly decreased immobility time and increased struggling time in the forced swim test, suggestive of an antidepressant-like effect. This preclinical evidence provides a potential approach for treating inflammation-related mental illness.